The Tradition of Zikir Ratib Saman in the Sammaniyah Order at the Great Mosque of Palembang - Andrew, Muhammad; Hakim, Lukman Nul; Hayati, Sofia (Program Studi Tasawuf dan Psikoterapi, 2023)
In order to combat the challenges of the immoral modern day, a social alternative, namely remembrance, is required. In truth, not everyone can adapt to modern developments, which include shifts in attitudes, resulting in a drop in morale. The goal of this research is to learn about the history of ratib saman remembrance at the Palembang Great Mosque, as well as the impact of ratib saman remembrance in dealing with modern-day challenges. This study employs qualitative research methods as well as descriptive research methods. In this study, data was collected through a series of processes, including observation, interviews, and documentation. Activities in qualitative data analysis are carried out in an interactive manner and continue until the data is full, ensuring the validity of the data.. Data analysis techniques employed include data reduction, data display, and conclusion drawing/verification. Data analysis presents facts in a systematic manner based on fact data obtained, allowing them to be easily understood and conveyed. According to the findings of this research, the Tarekat Sammaniyah began to spread to Indonesia at the end of the 18th century. Especially in Palembang, which was built around Syekh Abdus Samad Al Palembani's Great Mosque of Palembang (1737-1832M). The ratib saman remembrance tradition at the Palembang Grand Mosque has evolved over time in various areas of Palembang city. When reciting ratib saman for a long time, it has a positive impact, beginning with peace of mind, sustenance, changes in behavior, and worship is growing rapidly. Zikir ratib saman can be beneficial in dealing with the challenges of zikir ratib saman can help people overcome modern-day challenges and achieve happiness and peace of mind.